The Effect of Body Mass Index on Bleeding After on Pump Coronary Artery Bypass Grafting - Musfireh Siddiqeh; Imran Khan; Fakher-e- Fayyaz; Muhammad Awais Dawood; Syed Muzaffar Hasan Kirmani; Hannah Khurshid; Rehana Javaid (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the relationship of body mass index (BMI) and postoperative bleeding in patients undergoing isolated coronary artery bypass grafting (CABG) using cardiopulmonary bypass (CPB).